Mucosal Leishmaniasis caused by Leishmania (Viannia) braziliensis and Leishmania (Viannia) guyanensis in the Brazilian Amazon. - Jorge Augusto de Oliveira Guerra; Suzane Ribeiro Prestes; Henrique Silveira; Leila Inês de Aguiar Raposo Câmara Coelho; Pricila Gama; Aristoteles Moura; Valdir Amato; Maria das Graças Vale Barbosa; Luiz Carlos de Lima Ferreira (Public Library of Science (PLoS), 2011)
BACKGROUND: Leishmania (Viannia) braziliensis is a parasite recognized as the most important etiologic agent of mucosal leishmaniasis (ML) in the New World. In Amazonia, seven different species of Leishmania, etiologic agents of human Cutaneous Leishmaniasis, have been described. Isolated cases of ML have been described for several different species of Leishmania: L. (V.) panamensis, L. (V.) guyanensis and L. (L.) amazonensis. METHODOLOGY: Leishmania species were characterized by polymerase chain reaction (PCR) of tissues taken from mucosal biopsies of Amazonian patients who were diagnosed with ML and treated at the Tropical Medicine Foundation of Amazonas (FMTAM) in Manaus, Amazonas state, Brazil. Samples were obtained retrospectively from the pathology laboratory and prospectively from patients attending the aforementioned tertiary care unit. RESULTS: This study reports 46 cases of ML along with their geographical origin, 30 cases caused by L. (V.) braziliensis and 16 cases by L. (V.) guyanensis. This is the first record of ML cases in 16 different municipalities in the state of Amazonas and of simultaneous detection of both species in 4 municipalities of this state. It is also the first record of ML caused by L. (V.) guyanensis in the states of Pará, Acre, and Rondônia and cases of ML caused by L. (V.) braziliensis in the state of Rondônia. CONCLUSIONS/SIGNIFICANCE: L. (V.) braziliensis is the predominant species that causes ML in the Amazon region. However, contrary to previous studies, L. (V.) guyanensis is also a significant causative agent of ML within the region. The clinical and epidemiological expression of ML in the Manaus region is similar to the rest of the country, although the majority of ML cases are found south of the Amazon River.